"Refugees" and Others - Campbell, Erin (University of North Texas, 2016)
Refugees, a novel in progress, begins in the collective first-person with a group of people who live on the same residential street of middle-class homes in an east coast American city and are experiencing the most exquisitely vivid aurora borealis to appear in recorded history. But they quickly learn that this gorgeous wonder is a harbinger of civilization's demise and possibly the end of all life on the planet, because the solar storms causing the sky's fantastic nightly coloring is also slowly stripping away the atmosphere and leeching oxygen into space. This "we" narrative switches to third person, moving between two characters—Julie and Amira—as the narrative moves forward. The first chapter covers the first few months of this apocalyptic crisis, and Julie and Amira are central as they are forced decide if they still have the strength and the will to even attempt survival in these new and brutal circumstances. The second chapter, also told in third person, picks up seventeen years in the future with Aya, Amira's daughter who was six during the initial atmospheric disaster. A small group survived in an underwater refuge, recently discovered the atmosphere above had healed over time, and sent an excursion group, including Aya, to evaluate the changing environment. This chapter reveals the history and particular struggles of these characters living in this complex society, both residual and nascent. The third chapter returns to the group of neighbors—including Julie and Amira—seventeen years prior, immediately following the catastrophic event as their story continues to unfold. This chapter opens, like the first chapter, in the "we" voice, tracing the movement of the group south in a search for help and a desperate, though orderly, effort toward survival. This next phase of their journey introduces fresh conflicts and new characters and points to approaching challenges and the persistent hope for survival. Two short stories, unrelated to the novel and each other and entitled "Awake" and "Her," are also ...